Mindfulness-based cognitive therapy experiences in youth with inflammatory bowel disease and depression: findings from a mixed methods qualitative study. Issue 11 (4th November 2020) - Ewais, Tatjana; Begun, Jake; Kenny, Maura; Headey, Alan; Tefay, Merilyn; Kisely, Steve
Abstract : Objectives: Mindfulness-based cognitive therapy (MBCT) is effective in treating psychosocial comorbidities in inflammatory bowel disease (IBD); however, there have been no qualitative studies of MBCT experiences among youth with IBD. We aimed to examine the experiences of youth with IBD and depression who completed an adapted MBCT group programme, and the impact of common psychotherapy and group factors. Design: This mixed method qualitative study, nested within a randomised controlled trial (RCT) of MBCT for youth with IBD, employed thematic analysis of qualitative data from three focus groups and open-ended survey questions. Setting: The study was conducted in the outpatient department of a tertiary hospital for young adults in Brisbane, Australia. Participants: Out of sixty-four adolescents and young adults recruited to the RCT of MBCT for youth with IBD and depression, 29 completed the MBCT evaluation survey and 19 attended the focus groups. Results: Four key themes emerged: 'connectedness and shared understanding', 'growing in wisdom', 'therapeutic alliance' and 'barriers to mindfulness practice'. Participants described MBCT experiences as healing and transformative with the themes of connectedness, growing in wisdom and therapeutic alliance laying the foundation for therapeutic change. Main barriers included fatigue, depression, time and travel constraints. Conclusions: The study identified key themes facilitating the process of therapeutic change within the MBCT programme for youth with IBD and elucidated common and group psychotherapy factors underlying the key themes. Participants perceived connecting with peers as essential for learning mindfulness skills which in turn strengthened the connection. Study findings will facilitate interpretation of the results of the RCT of MBCT in youth with IBD and inform the design of future studies of MBCT in this cohort. Trial registration number: ACTRN12617000876392; Results.